Strengthening emotion-cognition integration. (2015) - Todd, Rebecca; Thompson, Evan
Abstract: Pessoa's (2013) integrative model of emotion and cognition can be strengthened in two ways: first, by clarification and refinement of key concepts and terminology, and second by the incorporation of an additional key neural system into the model, the locus coeruleus/norepinephrine system.